Antarala of the Shiva Temple 1 - Temples of India Project Team (Jio Institute, 2024)
The antarala (vestibule or antechamber) of Shiva Temple 1 is completely plain and simple. There are two niches on the lateral sides. The antarala leads to the garbhagriha (sanctum sanctorum). The door of the garbhagriha is plain, and there is no figure on the lalatabimba (lintel).